2022
DOI: 10.1021/acsami.2c08302
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding Laser-Induced Graphene Ultrasensitive Resonative Viral Sensors

Abstract: Early and reliable detection of an infectious viral disease is critical to accurately monitor outbreaks and to provide individuals and health care professionals the opportunity to treat patients at the early stages of a disease. The accuracy of such information is essential to define appropriate actions to protect the population and to reduce the likelihood of a possible pandemic. Here, we show the fabrication of freestanding laser-induced graphene (FLIG) flakes that are highly sensitive sensors for high-fidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Notably, the Oliver–Pharr model is valid for continuum materials. Previous studies showed that nanoscale structures, including nanofoams, obey continuum models. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the Oliver–Pharr model is valid for continuum materials. Previous studies showed that nanoscale structures, including nanofoams, obey continuum models. , …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that nanoscale structures, including nanofoams, obey continuum models. 34,55 Previous studies showed that the principal deformation mechanism in densely packed layered nanostructures is related to the relative slipping of the layers. 56,57 Therefore, the elastic properties of multilayered nanostructures are strongly influenced by interlayer interactions; namely, materials with strong interlayer forces will present higher stiffness than those with weak interlayer forces since the former materials are able to efficiently transfer shear stress between the layers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Researchers are currently using a mobile microcontrolled potentiostat and a LIGbased device to electrochemically quantify anti-SARS-CoV-2 antibodies in clinical blood samples. [97,98] Due to the conductivity of paper-LIG, it can be utilized for the sensing of temperature. [99] The resistance along this conductive path was then assessed in response to temperature changes between 20 and 45 °C, which were regulated by a Peltier element.…”
Section: Bioelectronicsmentioning
confidence: 99%
“…Researchers are currently using a mobile microcontrolled potentiostat and a LIG‐based device to electrochemically quantify anti‐SARS‐CoV‐2 antibodies in clinical blood samples. [ 97,98 ]…”
Section: Applicationsmentioning
confidence: 99%
“…Graphene is a two-dimensional (2D) hexagonal lattice of sp 2 carbon atoms that are covalently bonded within two planar directions . In addition to its high thermal and electrical conductivity, flexibility, and mechanical strength, graphene has an exceptionally high surface area (e.g., ∼2600 m 2 /g) and intrinsic theoretical capacitance (21 μF/cm 2 ). These properties perfectly poise this carbonaceous nanomaterial to be used within a broad array of applications ranging from electronics (e.g., supercapacitors) and biotechnology to environmental technology (e.g., renewable construction materials). Within the spectra of environmental technology, examples of graphene derivatives have been shown to be antibacterial by many researchers over the years . The potency of graphene-based materials is especially true in the presence of an applied voltage as exemplified by laser-induced graphene (LIG). , However, the exact mechanism for the antibacterial activity such as the physical destruction of the cell membrane via direct contact of the bacteria with the surface structure/texture chemical microbial toxicity such as oxidative stress, or electrical effects of LIG or other graphene-based materials remains ambiguous and can be attributed to any combination of the various mechanisms.…”
Section: Introductionmentioning
confidence: 99%